FEATURES OF ANTI-MÜLLERIAN HORMONE LEVELS IN OVARIAN HYPERANDROGENISM DEPENDING ON OBESITY TYPE AND FAT DISTRIBUTION - Yuldashev U. K.; Musakhodjaeva D. A.; Azizova Z. Sh. (The Conference Hub, 2026)
Ovarian hyperandrogenism (OHA) is associated with multi-level disturbances of folliculogenesis arising from the interplay of hormonal, metabolic, and immune-inflammatory pathways. The combined effects of body mass index (BMI), body fat distribution, and inflammatory cytokine milieu appear to exert an integrated influence on ovarian reserve, highlighting the need for a comprehensive assessment of these factors when predicting reproductive potential and tailoring individualized management strategies in women with OHA. Anti-Müllerian hormone (AMH) is widely regarded as a key biomarker of the functional follicular pool and a potential indicator of phenotypic heterogeneity in polycystic ovary syndrome (PCOS); however, available evidence on AMH variability across metabolic phenotypes and fat distribution patterns in hyperandrogenic patients remains limited (Ma Y.C. et al., 2025).